Global transcriptome analysis of rat dorsal root ganglia to identify molecular pathways involved in incisional pain. (September 2020) - Tran, Phu V; Johns, Malcolm E; McAdams, Brian; Abrahante, Juan E; Simone, Donald A; Banik, Ratan K
To develop non-opioid therapies for postoperative incisional pain, we must understand its underlying molecular mechanisms. In this study, we assessed global gene expression changes in dorsal root ganglia neurons in a model of incisional pain to identify pertinent molecular pathways. Male, Sprague–Dawley rats underwent infiltration of 1% capsaicin or vehicle into the plantar hind paw (n = 6–9/group) 30 min before plantar incision. Twenty-four hours after incision or sham (control) surgery, lumbar L4–L6 dorsal root ganglias were collected from rats pretreated with vehicle or capsaicin. RNA was isolated and sequenced by next generation sequencing. The genes were then annotated to functional networks using a knowledge-based database, Ingenuity Pathway Analysis. In rats pretreated with vehicle, plantar incision caused robust hyperalgesia, up-regulated 36 genes and downregulated 90 genes in dorsal root ganglias one day after plantar incision. Capsaicin pretreatment attenuated pain behaviors, caused localized denervation of the dermis and epidermis, and prevented the incision-induced changes in 99 of 126 genes. The pathway analyses showed altered gene networks related to increased pro-inflammatory and decreased anti-inflammatory responses in dorsal root ganglias. Insulin-like growth factor signaling was identified as one of the major gene networks involved in the development of incisional pain. Expression of insulin-like growth factor -2 and IGFBP6 in dorsal root ganglia were independently validated with quantitative real-time polymerase chain reaction. We discovered a distinct subset of dorsal root ganglia genes and three key signaling pathways that are altered 24 h after plantar incision but are unchanged when incision was made after capsaicin infiltration in the skin. Further exploration of molecular mechanisms of incisional pain may yield novel therapeutic targets.